Study of the structures of four-quark states in terms of the Born-Oppenheimer approximation - 刘学文 柯红卫 丁亦兵 李学潜 (Chinese physics C, 2015)
In this work, we use the Born-Oppenheimer approximation, where the potential between atoms can be approximated as a function of distance between the two nuclei, to study the four-quark bound states. By this approximation, Heitler and London calculated the spectrum of the hydrogen molecule, which includes two protons （heavy） and two electrons （light）. Cenerally, the observed exotic mesons Zb（10610）, ZD（10650）, Zc（3900） and Zc（4020） （Zc（4025）） may be molecular states made of two physical mesons and/or diquark-anti-diquark structures. Analogous to the Heitler-London method for calculating the mass of the hydrogen molecule, we investigate whether there exist energy minima for these two structures. Contrary to the hydrogen molecule case where only the spin-triplet possesses an energy minimum, there exist minima for both of these states. This implies that both molecule and tetraquark states can be stable objects. Since they have the same quantum numbers, however, the two states may mix to result in the physical states. A consequence would be that partner exotic states co-existing with ZD（10610）, Zb（]0650）, Zc（3900） and Zc（4020） （Zc（4025）） are predicted and should be experimentally observed.